Reading Capital in the Twenty-First Century: Thomas Piketty and political economy - David M. Kotz; Terrence McDonough; Cian McMahon (Revue de la Régulation)
This paper offers a radical political economy critique of Thomas Piketty’s Capital in the Twenty-First Century, drawing on heterodox economics and the social structure of accumulation (SSA) theory. We argue that the dynamics of inequality in capitalist systems cannot be fully explained at the level of capitalism in general, or by supplementing such an account with reference to state policies or contingent events, but require attention to the specific institutional form of capitalism.